Pengembangan media pembelajaran matematika sigeru buku pop-up berbasis etnomatematika materi kubus dan balok - Fatimah Dwie Hartanti; Sri Hariyani; Trija Fayeldi (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2020)
The learning media pop-up book with based etnomathematic use method of reasearch is research and development with the model is 4D. The purpose of research is to occurred aspect validity and practicality. The reaseach helpful in learning media is to be held a student’s interest and to use visual display in cube and beam lesson. A data collection using questionarry. Sample taking technique using simple random sampling with the number of samples based on the Slovin formula were at a fault 5%. Phase I test are a process of media validation and learning validation. Phase II test are a process practical test I was conducted by teacher and 8 students. Phase III test are a process practical test II was conducted by 30 students. The value of media and learning percentage is 92,3% and 86,636%  in highly valid category. 90,909% and highly practice category by phase I test. And then, the value by 30 students is 85,83% in highly practice category. The based on the result is a learning media pop-up book based etnomathematic can be using a learning media in the school.